Enhancing grinding parameters of TC4 titanium superalloy by using hybrid eco-friendly cooling system. (2022) - Kumar Singh, Sunil; Kumar Jha, Ashok; Ray, Amitava; Dewangan, Saurabh
Abstract: Grinding, a popular surface finishing operation with high dimensional accuracy is widely used for machining superalloy, ceramic, and composite materials. The trouble that arises while grinding is attributed to excessive specific energy consumption and high grinding zone temperature. This problem enhances for low thermal conductivity materials like TC4 titanium superalloy. An optimal method to minimize heat is the application of cutting fluids. However, the conventional method is inefficient and ineffective to penetrate coolant satisfactorily into the compact grinding zone. Therefore, to enhance the performance of TC4 titanium superalloy hybrid eco-friendly grinding which is the modern manufacturing process is used in this research work. Implementation of a hybrid cooling system using MQL coolant with a jet of Liquid CO2 at a higher feed rate provides a better surface morphology and eliminates biological problems. The experimental result shows that there is an eminently reduction of grinding force using a hybrid method as compared with conventional flood and MQL environmental conditions. This is generally due to better infiltration of fluid in the grinding zone and there is breakage of air turbulence which is formed around the porous grinding wheel. Moreover, MQL reduces overall manufacturing costs by reducing the amount of coolant and disposal difficulties. Significant reduction of heat flux was observed in a hybrid system which minimizes thermal-related problems and enhances the longevity of grinding wheel. [copyright information to be updated in production process]